2014
DOI: 10.1016/j.cell.2014.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing the Mouse Y Chromosome Reveals Convergent Gene Acquisition and Amplification on Both Sex Chromosomes

Abstract: Summary We sequenced the MSY (Male-Specific region of the Y chromosome) of the C57BL/6J strain of the laboratory mouse Mus musculus. In contrast to theories that Y chromosomes are heterochromatic and gene poor, the mouse MSY is 99.9% euchromatic and contains about 700 protein-coding genes. Only two percent of the MSY derives from the ancestral autosomes that gave rise to the mammalian sex chromosomes. Instead, all but 50 of the MSY's genes belong to three acquired, massively amplified gene families that have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
397
2
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(414 citation statements)
references
References 102 publications
14
397
2
1
Order By: Relevance
“…A recent report in mouse also suggests that amplification of Y-linked ampliconic genes is driven by the gene amplification of the gametologous X-linked gene pairs to restore an optimal sex ratio (36). However, in great apes, ampliconic regions on the Y and X are of different origin (37,38), suggesting that a mechanism to adjust sex ratio may not involve correlated amplification between gametologous gene pairs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report in mouse also suggests that amplification of Y-linked ampliconic genes is driven by the gene amplification of the gametologous X-linked gene pairs to restore an optimal sex ratio (36). However, in great apes, ampliconic regions on the Y and X are of different origin (37,38), suggesting that a mechanism to adjust sex ratio may not involve correlated amplification between gametologous gene pairs.…”
Section: Discussionmentioning
confidence: 99%
“…However, in other respects, the Anopheles and Drosophila Y are much more similar. More than one-third of the human Y chromosome and 99.9% of the mouse Y is euchromatic (56,62), whereas Drosophila and Anopheles Y chromosomes are entirely heterochromatic. Although relatively few in number, some ancestral X-Y gene pairs have been conserved throughout mammalian evolution because of their vital role as dosage-sensitive regulators of global gene expression (6,7).…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of map positions of these genes revealed no such physical overlap or proximity. We also investigated the distribution of miRNA genes among regions of the mouse X chromosome reported to be most highly conserved (the XCR region) (Graves et al, 1995) or more recently added during evolution (the XAR and New regions) (Graves et al, 1995;Soh et al, 2014). We found that all three types of miRNA loci are located predominantly in the more recently added regions of the X chromosome, with a preponderance (∼80%) of Type I miRNA genes mapping within the XAR region, whereas Type II and III miRNA genes were equally distributed among the XAR and New regions.…”
Section: Discussionmentioning
confidence: 99%